(untitled) (Journal of Nepal Geological Society, 2019)
Total 26 samples, 6 from river, 7 from deep tube well and 13 from shallow tube wells were analyzed for the isotopic composition and chemical composition of the water at different sources. The main focus of the study was to assess connection between aquifers, and recharge zone analysis of the local groundwater system in the Siraha and the Saptari Districts, west of the Koshi River. The δ18O composition of the Koshi River was found to be the lightest whereas the shallow tube wells at Haripur and Shambhunath were the heaviest. The δ18O composition at many locations showed identical values showing the correlation of water within the aquifers and also with the surface water. Based on the plot of δ18O vs δ2H, the shallow tube well at Asanpur and the deep tube well at Jamdahawere suspected to be recharged from the Kharak Khola. Similarly, the deep tube wells at Lalpur and Kusaha, the shallow tubes wellat Asanpur, Tudkiya and Raghunathpur, and the Mahuli Khola and the Khado Khola are interconnected. The deep tube wells at Tudkiya, Dhangadhi and Phulkakatti might have interconnection with the shallow tube wells at Khoriya and Golamukhsar.